DEVELOPMENT OF LEARNING MEDIA FOR THE GAME OF SNAKES AND LADDERS TO INCREASE STUDENTS LEARNING INTEREST IN THE PPKN SUBJECT FOR CLASS III SD NEGERI 024776 BINJAI - Nina Junisa Sianipar; Ramli Nur; Dede Ruslan (SENSEI RESEARCH CENTER, 2021)
This study aims to produce an innovative learning media product by developing learning media for snakes and ladders to be applied in the learning process. In this research the product is first validated by media experts and material experts. As well as assessment of responses from teachers and students. Products in the form of learning media for the game of snakes and ladders will be tested first in small groups and then in limited groups. The objectives of this study were (1) Obtaining the feasibility, practicality, and effectiveness of the snake and ladder learning media in PPKn subjects in class III SD Negeri 024776 Binjai from material experts and media experts, (2) Knowing the differences in interests and learning outcomes of students who use and not. using snake and ladder learning media in PPKn subjects in class III SD Negeri 024776 Binjai. Development This research was developed with the ADDIE development model, starting from the analysis, design stage, development stage, implementation stage, and evaluation stage. Based on the results of the analysis of experts consisting of material experts with an average value of 82.26, it means that it is very valid and with media experts with an average value of 89 it means very valid. The percentage value of classical completeness obtained by students in the pretest and posttest of the experimental group experienced a high increase, namely 40% to 95%, with an average pretest score of 59.00 and an average posttest score of 81.25. So that it has met the criteria for classical completeness and the learning media products have met the indicators of effectiveness and are suitable for use.